Catalyst‐Free Synthesis of 2, 3‐Benzodiazepines via Tetrahydrodiazirino[3, 1‐a]isoquinoline Reacts with Sulfonyl Chlorides. Issue 12 (25th March 2019) - Wang, Kaikai; Li, Yanli; Wang, Xiaoyu; Zhu, Baoku
Abstract: An unexpected process from tetrahydrodiazirino[3, 1‐ a ]isoquinolines and diversified sulfonyl chlorides RSO2 Cl (R=aryl, alkyl) to deliver highly yields 4, 5‐dihydro‐3H‐benzo[ d ][1, 2]diazepine skeleton compounds was disclosed via N ‐insertion ring‐opening reaction. The structural framework of 2, 3‐benzodiazepines is unambiguously confirmed by single‐crystal X‐ray crystallographic analysis. The present protocol features mild reaction conditions, high yields and feasibility of large‐scale synthesis and catalyst‐free access to benzo[2, 3]diazepines skeleton. In contrast, azomethine imines were produced by employing tetrahydrodiazirino[3, 1‐ a ]isoquinoline reacts with aroyl chlorides under the same conditions. Abstract : An unexpected process from tetrahydrodiazirino[3, 1‐ a ]isoquinolines and diversified sulfonyl chlorides to deliver highly yields 2, 3‐benzodiazepines compounds. In contrast, azomethine imines were produced by employing aroyl chlorides in this reaction under the same conditions.